Efficiency of Listed Manufacturing Firms in Jordan: A Stochastic Frontier Analysis - Al-Durgham, Lamees; Adeinat, Mohammad (International Journal of Economics and Financial Issues, 2020)
This study examines the technical efficiency of the manufacturing firms listed in Amman Stock Exchange market (ASE) in Jordan over the period 2009-2017. The stochastic frontier approach was used to measure the efficiency. The results show that the firms have an overall efficiency of 74 %, means that the firms wasted about 26% of their inputs. Among the firms, (RMCC) has the highest averageefficiency of (90% ) witha standard deviation of (0.06) over the period of the study, and (IPCH) has the lowest average efficiency of (26% )with a standard deviation of ( 0.38) for the same period. Keywords: Efficiency, manufacturing firms, stochastic frontier analysis, panel data JEL Classifications: D24, C51 DOI: https://doi.org/10.32479/ijefi.10489